Do Autocratic States Trade Less? - Aidt, Toke S.; Gassebner, Martin (World Bank, 2012)
Does the political regime of a country influence its involvement in international trade? A theoretical model that predicts that autocracies trade less than democracies is developed, and the predictions of the model are tested empirically using a panel of more than 130 countries for 1962–2000. In contrast to the existing literature, data on the regime type of individual countries are used rather than information about the congruence of the regime type of pairs of trading countries. In line with the model, autocracies are found to import substantially less than democracies, even after controlling for official trade policies. This finding is very stable and does not depend on a particular setup or estimation technique.